Safety and pharmacological efficiency (influence on muscular dysfunction) of new derivatives of chromon-3-aldehyde - A. V. Voronkov; D. I. Pozdnyakov; V. M. Rukovitsyna; E. T. Oganesyan (National Electronic Information Consortium (NEICON), 2020)
Objective: to estimate the safety of application of new derivatives of chromon-3-aldehyde and the possibility of its application for correction of muscular dysfunction. Materials and methods: the experiment was performed on 120 mice-males of the Balb/c line. Research objects - halogenated derivatives of chromon-3-aldehyde under codes of X3AF and X3ACl. The safety assessment of its application included the determination ofits single dose toxicity with calculation of LD50 using the Finni method. Further, the influence of derivatives on the development of muscular dysfunction using the myostimmulation test after its preventive introduction was studied. Results: the conducted research showed that new halogenated derivatives of chromon-3-aldehyde under codes of X3AF and X3ACl possessed an optimum profile of safety and wereable to alleviate the manifestations of muscle dysfunction. At the same time the substanceX3AF surpassed the substance X3ACl and comparison drug «Mildronat» in the size of pharmacological action. Conclusions: the low toxicity and high pharmacological efficiency of new halogenated derivatives of chromon-3-aldehyde makes these compounds the perspective ob